Princess Cyd [videorecording (DVD)] - Cone, Stephen, 1980-; Spence, Rebecca (Actress); Pinnick, Jessie; White, Malic; Meredith, James Vincent (Wolfe, 2017)
Eager to escape life with her depressive single father, 16-year-old athlete Cyd Loughlin visits her novelist aunt in Chicago over the summer. While there, she falls for Katie, a girl in the neighborhood, even as she and her aunt gently challenge each other in the realms of sex and spirit.